Análisis e interpretación financiero de los resultados de la actividad económica en la Constructura Chanpal S.A. tomando como base de estudio el periodo contable 2020 - Castro Morante, Ashley Milena (2021)
It is important to highlight the construction sector as a generator of a significant contribution to the Ecuadorian economy in terms of investment, production and employment level, adding to this the financial planning and optimization of financial management is important for the proper management of working capital in order to maintain optimal levels of liquidity and profitability in a company. The present case study consists of the analysis and financial interpretation of the results of the economic activity in the accounting period 2020 of the construction company Chanpal S.A., which has as objective to know the affectation caused by the bad management of the working capital in the liquidity and profitability of the company caused by the deficient financial planning carried out. The methodology used was based on descriptive research and the inductive method where the object of study was described and general conclusions were drawn. The bibliographic research consisted of the search and review of bibliographic material related to the object of study and the information used was the financial documentation provided by the company and documents obtained. Horizontal analysis and financial indicators were used for the financial interpretation of the financial statements. Adequate management of a company's working capital is fundamental to obtain high levels of profitability and liquidity; however, the results obtained show that poor asset management caused an excess of current liquidity and a decrease in asset turnover and ROA.